2016
DOI: 10.1038/oncsis.2016.56
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chromosome instability in Shugoshin-1 mice resulted in compromised glutathione pathway, activation of Wnt signaling and defects in immune system in the lung

Abstract: Mitotic error-mediated chromosome instability (CIN) can lead to aneuploidy, chromothripsis, DNA damage and/or whole chromosome gain/loss. CIN may prompt rapid accumulation of mutations and genomic alterations. Thus, CIN can promote carcinogenesis. This CIN process results from a mutation in certain genes or environmental challenge such as smoking, and is highly prevalent in various cancers, including lung cancer. A better understanding of the effects of CIN on carcinogenesis will lead to novel methods for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Consistent with the pathway analysis, CD8þ T-cells, Nkp46þ NK cells and Nkp1.1þ NK cells isolated from colonic tissues of untreated Sgo1 mice showed significant reduction in g-interferon production compared with control, indicating that Sgo1-CIN mice had partial immune dysfunction [149]. Various immune cell activation markers were downregulated in the lungs of Sgo1 mice [150]. In addition to increased generation of senescent cells, CIN model mice may accumulate senescent cells because immune surveillance is partly dysfunctional.…”
Section: Cin Can Enhance Carcinogenesissupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with the pathway analysis, CD8þ T-cells, Nkp46þ NK cells and Nkp1.1þ NK cells isolated from colonic tissues of untreated Sgo1 mice showed significant reduction in g-interferon production compared with control, indicating that Sgo1-CIN mice had partial immune dysfunction [149]. Various immune cell activation markers were downregulated in the lungs of Sgo1 mice [150]. In addition to increased generation of senescent cells, CIN model mice may accumulate senescent cells because immune surveillance is partly dysfunctional.…”
Section: Cin Can Enhance Carcinogenesissupporting
confidence: 76%
“…Collectively, these findings demonstrate that systemic CIN results in transcriptomic changes in metabolism, proliferation, cell fate, and immune responses in the colon, which may foster a microenvironment amenable to cancer development [149]. Lung RNAseq also indicated downregulations in immune function-related pathways, along with misregulations in other oncogenic pathways [150]. Thus, systemic CIN affects gene expressions in organ-specific and non-specific manners and can influence cancer development.…”
Section: Cin Can Enhance Carcinogenesismentioning
confidence: 82%
“…As aneuploidy alone also can modify global gene expression [66], can give proteotoxic stress to cells [67,68] and can modulate autophagy [69], genomic instability can have a broad impact on cellular physiology. The findings also suggest that such a CIN-specific gene expression signature and modulation of carcinogenic pathways can be targeted for cancer prevention purposes [64,65].…”
Section: Shugoshin 1 Haploinsufficient Mice (Sgo1-/+) Showed Cohesinomentioning
confidence: 82%
“…Using comparative RNAseq, we demonstrated that these cancer-prone organs (i.e. colon, liver, lung) differentially expressed genes with demonstrated cancer-association [64,65]. The results suggest that CIN alone can modify global gene expression and introduce local proneness (a field effect) to carcinogenesis.…”
Section: Shugoshin 1 Haploinsufficient Mice (Sgo1-/+) Showed Cohesinomentioning
confidence: 88%
See 1 more Smart Citation